PENETAPAN STATUS TERDAKWA OLEH PEMERINTAH KERAJAAN THAILAND PADA PEKERJA MIGRAN INDONESIA KORBAN PERDAGANGAN ORANG BERDASARKAN PROTOKOL PALERMO 2000: Determination of the Defendant’s Status Indonesian Migrant Worker Victim of Trafficking in Thailand Based on the 2000 Palermo Protocol - Viswari Anreany Nahan; Yulia Fitriliani (Reformasi Hukum Trisakti, 2024)
Protecting victims of trafficking in persons (TPPO) is the responsibility of every country that has ratified the 2000 Palermo Protocol. However, Thai police officers in performing their duties have made mistakes in determining the status of the defendant to six Indonesian illegal migrant workers (PMI) who are victims of TPPO. Related to that, the problem of this article is how the granting of defendant status to Indonesian citizens who are illegal migrant workers in Chiang Rai, Thailand, and how Thailand's responsibility for victims of TPPO occurs in its territory based on the 2000 Palermo Protocol. The article is a normative legal research and descriptive in nature, using secondary data, and data collection is done through literature study. The result and conclusion that can be obtained is that the granting of defendant status to six migrant workers is a violation of the 2000 Palermo Protocol because officers did not use the NRM Guidelines and violated Thailand's Anti-Human Trafficking Act B.E 2551. The Royal Thai Government has made efforts and progress in realizing its responsibility to protect victims of TPPO through its national laws.